Korelasi Alat Peraga KIT IPA dengan Motivasi Belajar Siswa Kelas V Sekolah Dasar - Amran, Muhammad; Hafid, Abd.; Hasma, Siti Nur (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research is a quantitative research with a correlational type of research which aims to determine the relationship between KIT Science teaching aids. Variable X in this research is KIT Science teaching aids and variable Y is student learning motivation. Based on the results of descriptive statistics, it was found that the KIT Science teaching aids had an average of 93.50 in the very good category and student learning motivation had an average of 95.58 in the very good category. Based on the results of inferential statistics, it shows rcount ≥ rtable (0.669 > 0.432) at the 5% significance level. Thus, H1 is accepted and H0 is rejected, so that the results of the research can be concluded that there is a significant relationship between KIT Science teaching aids and study motivation in fifth grade elementary school students.